Peran Modal Sosial Kelompok Tani pada Inovasi Program Perluasan Areal Tanam Baru (PATB) Padi di Desa Polokarto, Kecamatan Polokarto, Sukoharjo - Siti Zubaida; Retno Setyowati; Putri Permatasari (Jurnal Studi Inovasi, 2022)
The New Rice Planting Area Expansion Program (PATB) is a program from the government that was deliberately created due to the Covid-19 virus outbreak through SK (Decree) Number: 183/HK.310/C/8/2020. The purpose of the PATB rice program is to open new land for rice cultivation so that it is able to meet food needs during the Covid-19 virus. The targets of the PATB rice program are farmer groups. Social capital plays an important role in farmer groups in the implementation of the New Planting Area Expansion (PATB) program for rice. This study aims to determine the role of social capital in farmer groups in the implementation of the Rice New Planting Area Expansion (PATB) program in Polokarto Village, Polokarto District, Sukoharjo Regency. The research method used is descriptive qualitative. The results of the study indicate that the components of social capital that develop in farmer groups in Polokarto Village, Polokarto District, Sukoharjo Regency include trust, social norms, social networks, leadership, mutual cooperation, and participation in networks. Social capital plays a role in the implementation of the New Rice Planting Area Expansion (PATB) program, forming social values such as trust, social norms, social networks, leadership, mutual cooperation, participation in networks so that the New Planting Area Expansion (PATB) program for rice is well implemented. Keywords: Role, Social Capital, PATB Program